The Impact of Technology on Social Relations in Jordanian Society - Al-Srehan, Hussein (Journal of Ecohumanism, 2025)
The study aimed to demonstrate the impact of technology on social relations in Jordanian society, focusing on individuals who use modern technology, including the internet and social media, on a daily or almost daily basis. The descriptive-associative approach was adopted, where the research community was represented by Jordanian individuals of different age groups and genders throughout Jordan (North, Center, South). The sample of the study included 722 individuals; a special scale was developed to collect data on the impact of technology on social relations. The results of the study showed that the level of technological use was high among the respondents, while social relations were on average, and it also turned out that there was a noticeable impact of technology on social relations, with statistically significant differences in the level of impact based on demographic variables such as age and gender. The results have shown that the use of social media contributes to enhancing communication between individuals, but at the same time it may lead to some challenges in traditional relationships. The study recommends the need to promote the positive use of technology in Jordanian society, focusing on how to improve social relations through these means, in addition to the need to organize awareness programs to minimize possible negative effects.